Numerical Simulation of Flow Around Train : 2nd Report, Unsteady Aerodynamic Force on Tail Car - MAEDA, Tatsuo; SUZUKI, Masahiro; ARAI, Norio (Transactions of the Japan Society of Mechanical Engineers Series B, 1996)
It was recognized that the vibration amplitude of the tail car is greater, especially in a tunnel, than that of the other cars in a high-speed train. Though it has been noted that the aerodynamic force has some effect on the vibration of the train, few studies have been conducted and little knowledge has been gained. In this study, to clarify the aerodynamic effect on the train, a three-dimensional unsteady incompressible Navier-Stokes simulation was executed. Flows around the train both in an open section and in a tunnel section were simulated. Unsteady flow separation on the rear nose, which results in fluctuation of the yawing moment of the tail car, was obtained. In the tunnel section it was proven that the tunnel wall causes flow separation to be asymmetric and the expansion of the effective cross-sectional area of the flow between the tunnel wall and the train along the rear nose increases the pressure fluctuation. These factors result in the greater vibration in the tunnel section. We also presented a modified shape of the rear nose, which restrains flow separation and reduces the yawing moment fluctuation.